Sales and Markup Dispersion: Theory and Empirics - Monika Mrázová; J. Peter Neary; Mathieu Parenti (Center for Economic Studies and ifo Institute (CESifo), 2018)
We derive exact conditions relating the distributions of firm productivity, sales, output, and markups to the form of demand in monopolistic competition. Applications include a new “CREMR” demand function (Constant Revenue Elasticity of Marginal Revenue): it is necessary and sufficient for the distributions of productivity and sales to have the same form (whether Pareto, lognormal, or Fréchet) in the cross section, and for Gibrat's Law to hold over time; it implies a new class of distributions well-suited to capture the dispersion of markups; and it provides a parsimonious fit for the distributions of sales and markups superior to most widely-used alternatives.
Keywords: F15; F23; F12; 330; CREMR demands; Gibrat's Law; heterogeneous firms; Kullback-Leibler divergence; lognormal versus Pareto distributions; sales and markup distributions